Prevention and Management of Refeeding Syndrome - Andika Indrarespati; Kaka Renaldi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Refeeding Syndrome is a syndrome which occurs as a result of food administration in poorly nourished individuals. In this syndrome, there are wide range of biochemical alterations, clinical manifestations, and complications, starting from mild (asymptomatic) to severe (death). This syndrome was initially proposed in 1950s; however, there is still no agreement for its clear definition, causing clinicians to be less aware and tend to overlook this condition. Clinical manifestations which usually appear include electrolyte imbalances (hypophosphatemia, hypokalemia, hyponatremia, hypomagnesemia) and vitamin B1 deficiency. The main principle in management of refeeding syndrome is prevention, where clinicians need to identify this condition in the early stage in high risk individuals, supervision during refeeding, and administration of appropriate diet.